The use of Different Criteria Weighting and Multi-Criteria Decision Making Methods for University Ranking: Two-Layer Copeland - Abdulkerim Güler; Mesut Polatgil (Üniversite Araştırmaları Dergisi)
Multi-criteria methods have attracted attention in academia and industry applications for effective decision making. Although there are many multi-criteria decision making (MCDM) methods, none of these methods are perfect and should be chosen according to the decision problem. Choosing the necessary decision support method to find the right solution that is suitable for the decision maker becomes an important problem. To solve this problem, methods such as Copeland and Borda combining the results of different MCDM methods are available and widely used. In this study, a new hybrid model is proposed based on twice combining the results of different MCDM methods with different criterion weighting methods. The proposed model has been tested on student satisfaction data of 20 foundation universities in Turkey. It has been shown that the final model named Ensemble Copeland can be used as a benchmark in MCDM problems